Genetic variation in the rose pathogen Marssonina rosae estimated by RAPD - Werlemark, G.; Carlson-Nilsson, B. U.; Davidson, C. G. (International Journal of Horticultural Science, 2006)
Blackspot, caused by the fungus Marssonina rosae (Diplocarpon msae), is one of the most devastating and widespread diseases in garden roses, and it has as yet not been fully characterized in molecular terms. In this initial study we used RAPD analysis to investigate the genetic diversity among and within a few geographically diverse groups of single-spore isolates of M. rosae. DNA was extracted from in vitrogrown mycelia of 1 I single spore isolates grown on PDA medium. High levels of polymorphism were detected among the isolates. They clustered into three distinct groups: Group !consisted of isolates from eastern North America plus a European isolate (Germany), Group 2 included isolates from southern Sweden, and Group 3 included the isolates from Manitoba, Canada. The greater similarity of the environmental conditions in eastern North America and Europe as compared to the Canadian prairies suggest that. climate and weather could be key factors in influencing the potential race structure of M. rosae. However, variations among closely situated sites, e.g. southern Sweden, also occurred.